The Use of Instagram as Learning Media - Amanda, Sherly Herawati; Anggi Tias Pratama; Kartika Ratna Pertiwi (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2024)
The purpose of this literature review is to find out theoretical descriptions of the research methods used and find out the components in Instagram that can be made interesting for students to learn. Current technological developments such as Instagram over time can help the learning process outside and inside the classroom. The method used is looking for similarities, differences and providing views on the literature review. The results obtained from each study have different research methods based on the problems encountered. All teachers involve Instagram media as learning collaboration in achieving learning goals. The components in Instagram media that are of interest to students in learning are Instagram filters, feeds, Instagram stories and story highlights. The conclusion of this research is that journals (J1-J20) adopt various research methods to collect data and formulate conclusions related to certain problems. Some of them use the ADDIE development model as a basis.